The Interpretation of ΠΡΟΣ in Romans 3:26 - Hall, David (Tyndale bulletin, 2014)
In an article published in 1980, Richard Hays argued that Romans 3 should be seen as a unity. The whole chapter is an assertion of God’s integrity—that God is δίκαιος. Verses 21–26 ‘close the circle by answering the objections raised in verses 1–7’. Hays’s thesis has been largely rejected. S. K. Stowers stated in 1984 that Hays was ‘almost alone’ in stressing the internal coherence of the argument in Romans 3, and subsequent scholarship has largely concentrated on the analysis of specific sections of the chapter rather than on the chapter as a whole. My aim in this article is to support Hays’s thesis by examining verse 26, and in particular Paul’s use of the preposition πρός in that verse. [Introductory paragraphs]